BIMBINGAN BELAJAR BAHASA INGGRIS ANAK-ANAK DENGAN MEDIA LAGU DESA MEKAR INDAH - Marsiah Marsiah; Zahwa Karunia Wati; Fikry Alamsyah; Rauhunt Octavia Ninsy; Abdul Rahman; Vita Vita; Nurul Umam; Rajudin Rajudin; Aulia Ananda Febriani; Rahhmat Maulana; Husnul Khatimah (LPPM ITB AAS Indonesia Surakarta, 2023)
The ability to communicate in more than one language, or to be bilingual, is essential in today's globalised and technologically advanced world. Foreign language education is thus required to increase children's grasp of foreign language skills. However, the learning process occurs not only in school but also outside of school through tutoring. This tuition is intended to increase children's enthusiasm and motivation, as well as their English understanding. This learning tool's learning methods include lectures and learning through play, which includes the use of gaming skills such as sheets of paper, nursery song for children, and English learning animations. This learning aid is provided three times each week from 15:30 to 16:40. Based on the observation, the children are very enthusiastic and motivated to learn English.